2019
DOI: 10.1038/s41597-019-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity and change in the urban structure of metropolitan areas in the United States, 1990–2010

Abstract: While the population of the United States has been predominantly urban for nearly 100 years, periodic transformations of the concepts and measures that define urban places and population have taken place, complicating over-time comparisons. We compare and combine data series of officially-designated urban areas, 1990–2010, at the census block-level within Metropolitan Statistical Areas (MSAs) with a satellite-derived consistent series on built-up area from the Global Human Settlement Layer to create urban clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…While there are established geographical databases on natural land-cover that have been derived using consistent methodologies, until recently there has been no equivalent for urban land-cover types. Since 2000 there have been a number of initiatives at mapping population and building land-covers at global scales using earth observation data, census and building footprint information 24 26 . However, these need to be complemented by a landscape approach that can distinguish urban surfaces on a holistic basis, which accounts for the typical combination of micro-scale land-covers and associated physical properties.…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…While there are established geographical databases on natural land-cover that have been derived using consistent methodologies, until recently there has been no equivalent for urban land-cover types. Since 2000 there have been a number of initiatives at mapping population and building land-covers at global scales using earth observation data, census and building footprint information 24 26 . However, these need to be complemented by a landscape approach that can distinguish urban surfaces on a holistic basis, which accounts for the typical combination of micro-scale land-covers and associated physical properties.…”
Section: Background and Summarymentioning
confidence: 99%
“…The product is distinguished from other urban typologies (e.g. 26 , 28 , 29 ) which focus on individual aspects of urban cover (e.g. residential, commercial and industrial) without providing ancillary information.…”
Section: Background and Summarymentioning
confidence: 99%
“…In this section, we provide an overview of the various input data sets, including a discussion of the uncertainties. Such uncertainties may have considerable impacts on the ultimate estimates of persons, particularly when stratified along an urban-rural continuum in the LECZ, and must therefore be carefully understood (Gesch, 2018;Hawker et al, 2019;Uuemaa et al, 2020;Mondal and Tatem, 2012;Lichter et al, 2010;Leyk et al, 2019b). Since it has been shown that accuracy of the digital elevation models (DEMs) -upon which the LECZs are based -is highly sensitive to local conditions, including land cover, it is therefore sensible to evaluate a variety of DEMs that can be used to estimate population and land area in the LECZ.…”
Section: Methodsmentioning
confidence: 99%
“…By examining specific cities, we are able to better visualize and interpret fine-scale trends in classification over time. Here, we focus specifically on Atlanta and New York City, though bearing in mind that there is much heterogeneity in urban form, and change thereof, among the cities in the US [30]. The former is representative of cities of the sunbelt region that have experienced significant growth and expansion over the past half century.…”
Section: City-scale Census Analysis: Atlanta and New Yorkmentioning
confidence: 99%